Csf2 Attenuated Sepsis-Induced Acute Kidney Injury by Promoting Alternative Macrophage Transition - Li, Yiming; Zhai, Pan; Zheng, Yawen; Zhang, Jing; Kellum, John A.; Peng, Zhiyong (Frontiers in Immunology, 2020)
Sepsis is a systemic inflammatory state that occurs in response to infection and significantly increases mortality in combination with acute kidney injury (AKI). Macrophages accumulate in the kidney after injury and undergo a transition from a proinflammatory (M1) phenotype to an alternatively activated (M2) phenotype that is required for normal repair. However, the specific signals that regulate the transition from the M1 to M2 phenotype in vivo are unknown. Here, we found an unexpected role of Colony stimulating factor 2 (Csf2) in controlling macrophage transition in vitro and in a mouse model of sepsis induced by cecal ligation and puncture (CLP). We first co-cultured human M1 macrophages with HK-2 cells and characterized cytokine/chemokine profiles via Luminex. Of the cytokines and chemokines that were overexpressed in medium from M1 macrophages cocultured with human kidney-2 (HK-2) cells compared with that from M1 macrophages cultured alone, Csf2 and IL6 showed the greatest increases. Csf2 was exclusively secreted by HK-2 cells but not by M1 macrophages. Furthermore, recombinant human Csf2 protein promoted transition of M1 macrophages to the M2 phenotype in a dose and time-dependent manner. The apoptosis and reactive oxygen species (ROS) release induced by M1 macrophages in HK-2 cells was attenuated after exposure to exogenous Csf2. In addition, the switch from the proinflammatory M1 phenotype to the M2 phenotype occurred via the p-Stat5 pathway, which was activated by Csf2. Importantly, we found that intraperitoneal injection of a Csf2-neutralizing antibody after CLP aggravated kidney injury and suppressed tubular proliferation, subsequently decreasing survival. However, administration of recombinant mouse Csf2 protein could rescue mice with sepsis. Together, our results indicate that Csf2 plays critical roles in regulating macrophage transition via activation of p-STAT5. These data form a foundation upon which new therapeutic strategies can be designed to improve the therapeutic efficacy of cytokine-based treatments for sepsis-induced AKI.